2022
DOI: 10.1037/teo0000181
|View full text |Cite
|
Sign up to set email alerts
|

Epistemological foundations of humanistic psychology’s approach to the empirical.

Abstract: This article challenges the myriad criticisms of humanistic psychology's scientific status by directly confronting their common underlying claim: that humanistic psychology lacks an adequately empirical epistemological underpinning. Aristotelian epistemology is shown to be foundational to humanistic psychology's approach to the empirical in contradistinction to the tradition of positivistic empirical psychology, the epistemological roots of which lie primarily in atomism. Core characteristics of humanistic psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, some scholars made qualitative distinctions between the two. For example, the two views differ in their beliefs regarding whether research should (can) be how to conceptualize human nature, and the role of interpretation in research (Crotty, 1998;Waterman, 2013;DeRobertis, 2021). Considering these fundamental differences, it is not surprising that Jiang started to integrate qualitative research methods in his research practice and view a different future of counseling psychology after he found the values of traditional Chinese wisdom in his 1960s.…”
Section: Clientmentioning
confidence: 99%
“…Nevertheless, some scholars made qualitative distinctions between the two. For example, the two views differ in their beliefs regarding whether research should (can) be how to conceptualize human nature, and the role of interpretation in research (Crotty, 1998;Waterman, 2013;DeRobertis, 2021). Considering these fundamental differences, it is not surprising that Jiang started to integrate qualitative research methods in his research practice and view a different future of counseling psychology after he found the values of traditional Chinese wisdom in his 1960s.…”
Section: Clientmentioning
confidence: 99%